Pengaruh Perilaku Kewirausahaan, dan Modal Usaha terhadap Pelaksanaan Informasi Akuntansi Usaha Mikro Kecil (UMK) di Desa Kaeneno Kecamatan Fautmolo - Firson Metboki; Apriana H.J. Fanggidae; Minarni Anaci Dethan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This researcher aims to determine the influence of entrepreneurial behavior, business capital in the implementation of MSE accounting information in Kaeneno Village, Fautmelolo District. This study uses a quantitative approach. The number of samples used in this study was 35 respondents using primary data. The data collection technique uses a coordinator distributed to MSE business actors in Kaeneno Village, Fautmelolo District. The data analysis techniques used in this study are descriptive, multiple linear analysis, hypothesis test and coefficient of determination. The results of the study show that the variables of entrepreneurial behavior have an effect on the use of accounting information and business capital has a simultaneous effect on the use of accounting information.